Doing Business in the European Union 2020 : Greece - World Bank Group (World Bank, Washington, DC, 2020)
Doing Business was the first global indicator created to measure aspects of regulation that enable or hinder the owners of small and medium-size businesses in starting, operating or expanding their companies. In its annual publication, each economy is represented by its largest business city and compared globally with another one hundred and eighty-seven economies. Doing Business in the European Union 2020 Greece benchmark twenty-four additional cities, capturing regional differences in regulations and their enforcement. This report highlights the divergence in regulatory performance among six Greek cities and suggests ways to bridge the implementation gap and converge toward best regulatory practices in the five areas benchmarked.